Comparison of Two Standard Treatment Approaches in Locoregionally Advanced Nasopharyngeal Carcinoma - Mohamad, Issa; Abu-Hijleh, Fawzi; Mayta, Ebrahim; Abu-Hejleh, Taher; Al-Gargaz, Wisam; Al Mousa, Abdellatif; Abu-Hijlih, Ramiz; Hosni, Ali (South Asian Journal of Cancer, 2022)
Objectives To compare outcomes and toxicity of two standard treatment approaches of advanced nasopharyngeal carcinoma (NPC).Methods Between 2010 and 2016, patients with NPC, stage II–IVa, treated with induction chemotherapy (IC) (TPF), followed by concurrent chemoradiotherapy (CCRT) (induction group), or CCRT, followed by adjuvant chemotherapy (AC) (PF) (no-induction group), were retrospectively reviewed. CCRT included platinum-based chemotherapy with intensity-modulated radiotherapy. Survival outcomes, the pattern of failures, toxicity, and predictors for survival outcomes were evaluated.Results A total of 110 patients were included, 65 in the induction group and 45 in the no-induction group. There were no significant differences in the DFS and overall survival (OS) at 3 years between the two groups. On multivariate analysis, performance status (1 vs. 0) predicted worse OS. The 3-year cumulative incidence rates for local, regional, and distant failures were 58.5% (95% confidence interval [CI]: 8.4–89%), 58.00% (95% CI: 8–88.8%), and 63.90% (95% CI: 14.1–90.2%), respectively. IC had more frequent acute grade (G) II anemia (13 vs. 1, p < 0.01), late G II brain toxicity (4 vs. 1, p < 0.01), and late G II dysphagia (32 vs. 11, p = 0.01).Conclusions Survival outcomes were comparable between the two groups. IC had more frequent acute G II anemia and late G II brain and esophageal toxicities.
Keywords: nasopharyngeal carcinoma; IMRT; outcomes; toxicity; induction chemotherapy; concurrent chemotherapy